PWE-066 Pre-analytical and analytical variability in laboratory practice could affect calprotectin accuracy between uk sites; the results of a national laboratory questionnaire. (22nd June 2015) - Brookes, MJ; Gama, R; French, J; Ford, C; Whitehead, S; Folkes, J; Hayee, B; Robins, A; Logan, R; Steed, H
Abstract : Introduction: Faecal calprotectin (f-Cp), a calcium binding protein, is a product of mucosal granulocyte infiltration in Inflammatory Bowel Disease (IBD). In 2003 a national survey identified that 0.5% of UK laboratories offered an assay to measure f-Cp, but variability in practice was demonstrated between these laboratories. In 2013 NICE supported the use of f-Cp in the UK to diagnose IBD. However we have previously reported inter-assay variability, which may limit the efficacy of this test. Method: The aim of this study was to evaluate variability in pre-analytical and analytical evaluation of f-Cp by laboratories across the UK. We designed and undertook a questionnaire evaluation of all laboratories in the UK who currently perform an f-Cp assay and are members of the national quality assessment programme. Results: The questionnaire was sent to 59 laboratories in the UK and responses were received from 69% (n = 41). The following commercial assays were used; Buhlmann ELISA 36.6% (n = 15); Thermo Phadia EliA ELISA 22.0% (n = 9); Quantum Blue 17.1% (n = 7); Immundiagnostik ELISA 12.2% (n = 5). The assay reporting range was limited by the laboratory in 92.7% of cases (n = 38); the upper limit being 300ug/g in 12.2% (n = 5) and 600ug/g in 24.4% (n = 10). 29.3% (n = 12) run the assay manually, whereas the remainder use automated platforms. 82.9% (n = 34) laboratories stored stool specimens before analysis whereas 17.1% extracted calprotectin immediately and stored extract. Those storing stool did so as follows: 55.9% (n = 19) at 4–8ºC; 38.2% (n = 13) at -20˚C; and 2.9% (n = 1) at -40˚C. Stool or extract samples were stored by laboratories for the following durations: less than 1 week by 65.9% (n = 27); 1 week only by 19.5% (n = 8); 2 weeks by 7.3% (n = 3). Stool extraction was performed either by manual weighing (26.8%; n = 11) or by a variety of extraction devices. For watery samples the assay would not be performed by 12.2% (n = 5) of sites. Samples containing blood were rejected by 12.2% (n = 5) of sites. 39.0% (n = 16) of laboratories would provide an amended clinical report for processed watery specimens, and 42.5% (n = 17) would provide the same if contaminated with blood. Conclusion: Laboratory practices vary widely and there is little standardisation of pre-analytical and analytical stages in measuring f-Cp. In addition the use of different assays by sites across the UK could interfere with the accuracy of calprotectin reporting. These practice variances are likely to further confound f-Cp accuracy which we have previous reported as being assay dependent. Disclosure of interest: M. Brookes Grant/Research Support from: Vifor international, Speaker Bureau of: Warner Chilcott, R. Gama: None Declared, J. French: None Declared, C. Ford: None Declared, S. Whitehead: None Declared, J. Folkes: None Declared, B. Hayee: None Declared, A. Robins: None Declared, R. Logan: None Declared, H. Steed: None Declared.